Connected Fitness: Students' Views on Online Physical Education Learning - Darin Jan Tindowen; Jayvin Taguba (Formosa Publisher, 2024)
This study aims to assess students' experiences in learning Physical Education in an online environment. A descriptive research design was utilized to evaluate the experiences of 615 college students enrolled in Physical Education courses during the second semester of the 2020-2021 academic year at a higher education institution in Northern Philippines, amid the COVID-19 pandemic. Participants were selected through stratified random sampling and provided feedback via a standardized questionnaire. Data analysis employed descriptive statistics, including frequency, percentage, and weighted mean. Findings revealed that students actively engaged with online Physical Education classes, primarily using cellular phones and laptops, reflecting adaptability to this learning format. While students reported difficulties in achieving skill improvement compared to traditional in-person classes, many noted a sense of personal progress and appreciated the support and communication offered throughout the online learning experience. These insights highlight both the challenges and successes of online Physical Education during an unprecedented time.